Actigraphic sleep measures and diet quality in the Hispanic Community Health Study/Study of Latinos Sueño ancillary study. (28th March 2017) - Mossavar‐Rahmani, Yasmin; Weng, Jia; Wang, Rui; Shaw, Pamela A.; Jung, Molly; Sotres‐Alvarez, Daniela; Castañeda, Sheila F.; Gallo, Linda C.; Gellman, Marc D.; Qi, Qibin; Ramos, Alberto R.; Reid, Kathryn J.; et al.
Summary: Using a cross‐sectional probability sample with actigraphy data and two 24‐h dietary recalls, we quantified the association between sleep duration, continuity, variability and timing with the Alternative Healthy Eating Index‐2010 diet quality score and its components in 2140 Hispanic Community Health Study/Study of Latinos participants. The Alternative Healthy Eating Index diet quality‐2010 score ranges from 0 to 110, with higher scores indicating greater adherence to the dietary guidelines and lower risk from major chronic disease. None of the sleep measures was associated with total caloric intake as assessed using dietary recalls. However, both an increase in sleep duration and sleep efficiency were associated with healthier diet quality. Each standard deviation increase in sleep duration (1.05 h) and sleep efficiency (4.99%) was associated with a 0.30 point increase and 0.28 point increase, respectively, in the total Alternative Healthy Eating Index‐2010 score. The component of Alternative Healthy Eating Index‐2010 most strongly associated with longer sleep duration was increased nuts and legumes intake. The components of Alternative Healthy Eating Index‐2010 most strongly associated with higher sleep efficiency were increased whole fruit intake and decreased sodium intake. Both longer sleep duration and higher sleep efficiency were significantly associated with better diet quality among US Hispanic/Latino adults. The dietary components most strongly associated with sleep duration and sleep efficiency differed, suggesting potentially independent mechanisms by which each aspect of sleep impacts dietary choices. Longitudinal research is needed to understand the directionality of these identified relationships and the generalizability of these data across other ethnic groups.